Executive Dysfunction, Psychiatric Symptoms, and Behavioral Dysregulation in Preschoolers: Preliminary Findings in a Clinical Sample. Issue 1 (2nd January 2023) - Martin, Sarah E.; Kavanaugh, Brian C.; Paszek, Claudia; DeMarco, Mia; Mernick, Lauren R.; Boekamp, John R.
ABSTRACT: Children with deficits in executive function are at risk for poor outcomes in academic, social-emotional, and behavioral domains. These deficits have been particularly well documented in school-aged children with attention-deficit/hyperactivity disorder (ADHD) and disruptive behavior disorders. However, there have been fewer studies exploring the links between executive function and psychopathology in preschool-aged children, particularly among young children with diagnosed psychiatric disorders and significant clinical impairment. This study examined associations between executive dysfunction, psychiatric symptoms, and behavioral dysregulation in a sample of 44 preschoolers participating in an intensive psychiatric day treatment program. The NIH Toolbox Early Childhood Cognition Battery was used to assess EF, including inhibitory control and cognitive flexibility, and parent-reported assessments were used to examine child psychiatric symptoms and behavioral dysregulation. Analyses using linear and logistic regression equation modeling suggest that executive dysfunction – particularly cognitive inflexibility – is a significant predictor of ADHD symptoms and behavioral dysregulation in clinically-referred preschoolers. Findings are discussed with respect to the role of executive dysfunction in early childhood psychopathology, with implications for treatment. Findings also suggest the NIH Toolbox is feasible for use in an early childhood psychiatric treatment setting and provides valid neurocognitive results to inform treatment planning and clinical care.